2020
DOI: 10.19173/irrodl.v21i2.4578
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Service Recovery Satisfaction in an Open and Distance Learning Higher Education Institution in Malaysia

Abstract: This study investigated the relationships among justice dimensions (distributive, procedural, interpersonal, and informational), university image, service recovery satisfaction, and customer behavioural outcomes (trust, word of mouth, repurchase intention, and loyalty). This study adopted a cross-sectional survey approach and data were collected through a survey of 303 students of Open University Malaysia in Malaysia who experienced service failure and service recovery. The framework was tested via partial lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Online learning has been established as an effective and influential learning medium in many educational organizations and institutions (Ahmed Abdullah & Sultana Mirza, 2020;bin Mohd Amin, Kumar Piaralal, Rosli bin Daud, & bin Mohamed, 2020;Lee, Chang, & Bryan, 2020;Westine et al, 2019). Online courses provide a convenient and flexible approach to learning, and students have the option of studying even when they are working (Kim, Liu, & Bonk, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Online learning has been established as an effective and influential learning medium in many educational organizations and institutions (Ahmed Abdullah & Sultana Mirza, 2020;bin Mohd Amin, Kumar Piaralal, Rosli bin Daud, & bin Mohamed, 2020;Lee, Chang, & Bryan, 2020;Westine et al, 2019). Online courses provide a convenient and flexible approach to learning, and students have the option of studying even when they are working (Kim, Liu, & Bonk, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…When there is mutual trust among members of a knowledge-sharing group, each member will assume that the shared knowledge is being used appropriately and will not be used to counteract or undermine their individual capabilities (Staples and Webster, 2008). Furthermore, in an online learning environment, where interactions are limited to on-screen written and oral telecommunications, a feeling of trust will reduce anxiety about the risks associated with the information being disclosed (bin Mohd Amin et al, 2020). McEvily et al (2003) demonstrated that with trust, the recipient does not need to spend time and effort to verify the accuracy of the acquired knowledge but can use it immediately.…”
Section: The Moderating Role Of Trust Between Knowledge Sharing and S...mentioning
confidence: 99%
“…Specifically, the transition from traditional learning to distance learning, one of the urgent measures adopted to minimize the spread of COVID-19, posed numerous challenges for universities and students (Eli-Chukwu et al ., 2023; Adedoyin and Soykan, 2020). Although online learning had been an effective means of knowledge acquisition in many institutions prior to the pandemic (Neneh, 2020; bin Mohd Amin et al ., 2020), it appeared that the speed in which this transition occurred during the pandemic was both unprecedented and overwhelming (Rana, 2022), in addition to adversely affecting students' activities and academic performance (Adedoyin and Soykan, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation